An educational video on long-acting reversible contraception as a counseling tool for postpartum adolescents - Somsook Santibenchakul; Kittithorn Thanativakul; Unnop Jaisamrarn (BMC, 2022)
Abstract Objective To assess the effects of using an animated local language educational video to counsel postpartum adolescents on the benefits and use of long-acting reversible contraception (LARC). Materials and methods A two-stage, single group, experimental study was conducted. A total of 124 female adolescents aged < 20 years who had given birth within the last six weeks participated in the study. An educational video and a questionnaire were developed and validated. Participants were asked to fill out a questionnaire on basic demographic data, contraception preferences, and 10 true/false statements to test general contraceptive knowledge, after which they were shown an educational video in a private room. Following this, participants completed the second part of the questionnaire that assessed their knowledge using the same true/false statements and contraception preferences administered earlier. Results The mean age (standard deviation) of participants was 18.1 (1.5) years. Participants' mean age (SD) at the time of their first sexual intercourse was 16.2 (1.6) years. Among the 124 participants, 31 (25%) indicated that they would use LARC before viewing the educational video. After viewing the educational video, this number increased to 48 (38.7%). The participants' knowledge score was independently associated with their preference to select LARC (adjusted odds ratio 1.46, 95% confidence interval 1.09- 1.97). Conclusion This study demonstrated that counseling tools such as animated local language educational video might effectively improve contraceptive knowledge and the preference for LARC in postpartum adolescents. An educational video regarding LARC could be used as a counseling tool for postpartum adolescents.